Genomic Profiling of HER2‐Positive Gastric Cancer: PI3K/Akt/mTOR Pathway as Predictor of Outcomes in HER2‐Positive Advanced Gastric Cancer Treated with Trastuzumab. (26th April 2018) - Díaz‐Serrano, Asunción; Angulo, Barbara; Dominguez, Carolina; Pazo‐Cid, Roberto; Salud, Antonieta; Jiménez‐Fonseca, Paula; Leon, Ana; Galan, Maria Carmen; Alsina, Maria; Rivera, Fernando; Plaza, J. Carlos; Paz‐Ares, Luis; et al.
Abstract: Background: HER2‐positive gastric cancer (GC) affects 7%–34% of patients with GC. Trastuzumab‐based first‐line treatment has become the standard of care for HER2‐positive advanced gastric cancer (AGC). However, there are no clinically validated biomarkers for resistance to HER2‐targeted therapies. Upregulation of PI3K pathway and tyrosine kinase receptor (TKR) alterations have been noted as molecular mechanisms of resistance in breast cancer. Our study aimed to perform a molecular characterization of HER2‐positive AGC and investigate the role of PI3K/Akt/mTOR signaling pathway activation and TKR gene copy number (GCN) gains as predictive biomarkers in HER2‐positive AGC treated with trastuzumab. Patients and Methods: Forty‐two HER2‐positive GC samples from patients treated with trastuzumab‐based first‐line chemotherapy were selected. DNA samples were sequenced. PTEN and MET immunohistochemistry were also performed. Results: Concurrent genetic alterations were detected in 97.1% of HER2‐positive AGC. We found activation of PI3K/Akt/mTOR pathway in 52.4% of patients and TKR GCN gains in 38.1%. TKR GCN gains did not correlate with overall survival (OS) or progression‐free survival (PFS). Multivariate Cox models showed that PI3K/Akt/mTOR activation negatively affects the effectiveness of trastuzumab‐based chemotherapy in terms of OS and PFS. Conclusion: Our results provide for the first time a detailed molecular profile of concurrent genetic alterations in HER2‐positive AGC. PI3K pathway activation could be used as a predictive marker of worse outcome in this patient population. In addition, gains in copy number of other TKR genes in this subgroup may also influence the survival benefit obtained with trastuzumab. Implications for Practice: This article reports, for the first time, a detailed molecular profile of genomic alterations in patients with HER2‐positive advanced gastric cancer (AGC). PI3K/Akt/mTOR signaling pathway activation seems to have a differentially negative effect on overall survival and progression‐free survival in AGC treated with trastuzumab‐based chemotherapy. Combining different targeted agents could be a successful therapeutic strategy to improve the prognosis of HER2‐positive AGC. Abstract : This article describes genomic profiling of patients with HER2‐positive advanced gastric cancer who were treated with first‐line trastuzumab‐based chemotherapy, focusing on whether PI3K/Akt/mTOR pathway status could be relevant in selecting suitable patients for targeted therapies.